The status of ponds in the western SORDU project area - Cossins, N.J. (International Livestock Centre for Africa, 1983)
Discusses the construction & utilisation of ponds in the Borana system of pastoral production in Sidamo, Ethiopia, with particular reference to pond size, selection of site, usability status, and organisation of ownership & maintenance.